Decreased GABA-A Receptor Binding in Association With β-Lactam Antibiotic Use. (December 2019) - Flaus, Anthime; Riaño Barros, Daniela Alexandra; Hinz, Rainer; Myers, James F.; Lingford-Hughes, Anne; Koepp, Matthias J.; Hammers, Alexander; McGinnity, Colm Joseph
Abstract : Abstract: β-Lactam antibiotics are proconvulsive. In laboratory animals, this effect seems to be predominantly mediated through inhibition of GABA-A receptors, but it has not been demonstrated in humans in vivo. We report images of a [ 11 C]Ro15-4513 PET from a 40-year-old man who had completed a 1-week course of flucloxacillin before it. Relative to healthy controls, the participant had significantly lower mean gray matter binding. These novel data suggest that, in humans, the proconvulsive effect of β-lactam antibiotics is mediated via either competition for the same benzodiazepine-binding site as [ 11 C]Ro15-4513 or downregulation of GABA-A receptor expression.